Otimização do atendimento médico-hospitalar emergencial utilizando sistema a eventos discretos - Santos, Luciano Eduardo Braga dos (2016)
This work prop oses numerical metho d of simulation and optimization of waiting time in queues in hospital emergency. The case study is carried out in private hospital in the city of Goiania, Goias/Brazil. It is used to mo del discrete event systems as computational simulator and two optimization heuristics: the Brute Force algorithm and Genetic Algorithm. The optimization results are compared with the directives found in Resolution CFM 2077/2014, in an attempt to adapt the system to this resolution. With the results, it is observed that the simulation metho d and optimization metho ds are efficient to minimize queues at hospital emergency system.